Effect of geographic isolation on genetic variation and population structure of Euphrasia nankotaizanensis, a threatened endemic alpine herb in Taiwan. Issue 3 (March 2023) - Chen, Syuan-Yu; Huang, Chi-Chun; Cheng, Yu-Tzu; Wang, Chih-Chiang; Li, Chiuan-Yu; Lai, I-Ling; Hung, Kuo-Hsiang
Abstract: Euphrasia nankotaizanensis (Orobanchaceae) is a rare alpine herb that is endemic to Taiwan. Only four small populations remain in Xue, Nanhu, and Cilai Mountains of Taiwan. The distribution of alpine herbs is severely threatened by climate change, which influences genetic variation and population structure. In this study, we investigated the effects of the natural isolation of alpine habitats on the genetic diversity and geographic structure of populations of E. nankotaizanensis using chloroplast (cp) and nuclear DNA (nrDNA) markers. We found lower levels of genetic diversity in E. nankotaizanensis than in other alpine plants and little to no genetic variation within populations, which could be mainly attributed to the small population size and genetic drift. Only one nrDNA haplotype was present in each population. The lack of monophyly of the four populations in cpDNA probably resulted from lineage sorting or occasional long-distance seed dispersal. Phylogeographic analysis suggested that Nanhu Mountain was probably a refugium over the glacial maxima, agreeing with the potential refugia in central Taiwan. T he STRUCTURE and AMOVA analyses revealed significant genetic differentiation in nrDNA among the mountains, which resulted from geographical isolation among these mountains. Estimates of the effective population size (Ne) and demography reflected lower Ne values and a recent population decline, probably implying a greater extinction risk for E. nankotaizanensis . We observed genetic depletion and considerable genetic differentiation among mountain populations, which should be considered in future conservation efforts for this species. In addition, this study provides important insights into the long-term potential of alpine herbs in Taiwan, which are useful for a better prediction of their responses to future climate change.